Rapport sur l'activité de l'Institut en1933-34 - Gilson, G. (Ostende : Institut d'Etudes Maritimes, 1935)
Bibliotheek E. Anseele
Dedicator: Gilson, G., dedicatee: Anseele, Edward (sr.)
Frans
Verslag
Keywords: visserij